A replacement for Trident – can the UK afford it?. (1st February 2010) - Burt, Peter
Cash shortages caused by the credit crunch will force the UK's next government to choose between replacing the Trident nuclear weapons system and meeting flagship social policy goals. Replacing Trident will be a high risk project because a long lead-in time means that changing circumstances may make new nuclear weapons far less relevant to national security needs by the time they enter service. Global climate change is emerging as a major future security challenge, but it is not clear what role nuclear weapons can play in addressing this threat. Expenditure on nuclear weapons could consume resources that might otherwise be used in the fight against climate change and climate change is itself one of the drivers which will influence the long-term affordability of nuclear weapons. The credit crunch is likely to magnify the risks associated with replacing Trident and compound pressure on the affordability of Britain's nuclear weapons.